IL-23 plays a key role in Helicobacter hepaticus-induced T cell-dependent colitis. - Kullberg, M; Jankovic, D; Feng, C; Hue, S; Gorelick, P; McKenzie, B; Cua, D; Powrie, F; Cheever, A; Maloy, K; Sher, A (2006)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract that is caused in part by a dysregulated immune response to the intestinal flora. The common interleukin (IL)-12/IL-23p40 subunit is thought to be critical for the pathogenesis of IBD. We have analyzed the role of IL-12 versus IL-23 in two models of Helicobacter hepaticus-triggered T cell-dependent colitis, one involving anti-IL-10R monoclonal antibody treatment of infected T cell-sufficient hosts, and the other involving CD4+ T cell transfer into infected Rag-/- recipients. Our data demonstrate that IL-23 and not IL-12 is essential for the development of maximal intestinal disease. Although IL-23 has been implicated in the differentiation of IL-17-producing CD4+ T cells that alone are sufficient to induce autoimmune tissue reactivity, our results instead support a model in which IL-23 drives both interferon gamma and IL-17 responses that together synergize to trigger severe intestinal inflammation.